Advancing chemical safety assessment through an omics-based characterization of the test system-chemical interaction - del Giudice, Giusy; Migliaccio, Giorgia; D’Alessandro, Nicoletta; Saarimäki, Laura Aliisa; Torres Maia, Marcella; Annala, Maria Emilia; Leppänen, Jenni; Mӧbus, Lena; Pavel, Alisa; Vaani, Maaret; Vallius, Anna; Ylä‐Outinen, Laura; et al. (Frontiers in Toxicology, 2023)
Assessing chemical safety is essential to evaluate the potential risks of chemical exposure to human health and the environment. Traditional methods relying on animal testing are being replaced by 3R (reduction, refinement, and replacement) principle-based alternatives, mainly depending on in vitro test methods and the Adverse Outcome Pathway (AOP) framework. However, these approaches often focus on the properties of the compound, missing the broader chemical-biological interaction perspective. Currently, the lack of comprehensive molecular characterization of the in vitro test system results in limited real-world representation and contextualization of the toxicological effect under study. Leveraging omics data strengthens the understanding of the responses of different biological systems, emphasizing holistic chemical-biological interactions when developing in vitro methods. Here, we discuss the relevance of meticulous test system characterization on two safety assessment relevant scenarios and how omics-based, data-driven approaches can improve the future generation of alternative methods.